DAKWAH MUSLIM DESIGNER COMMUNITY MELALUI DESAIN GRAFIS - AR, Nirwan Wahyudi (Jurnal Dakwah Tabligh, 2022)
The study was qualitative field research using the sociological and da’wah sciences approaches. The primary data source of the study was 20 (twenty) members of the Muslim Designer Community (MDC), while the secondary data sources were readings or references related to the study topic. Open interview, participant observation, and document review were utilized in collecting the data, which were then analyzed through the phenomenological data analysis technique. MDC graphic da’wah activities, both in the real world and in cyberspace (internet) reflected two major dimensions of da’wah activities, namely the dimensions of treatise delivery (bi Ahsan al-qawl) and of the obedience or the application of truth values (bi Ahsan al-’amal). MDC interpreted the graphic da’wah activities as a form of visual da’wah, a marker of changes in society’s perception of dakwah, a reflection of contemporary da’wah movements, a possible visualizer counterpart, and a driver for the unification of the da’wah visualizers.